2022
DOI: 10.1007/s43979-022-00002-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress of quantum dots for energy storage applications

Abstract: The environmental problems of global warming and fossil fuel depletion are increasingly severe, and the demand for energy conversion and storage is increasing. Ecological issues such as global warming and fossil fuel depletion are increasingly stringent, increasing energy conversion and storage needs. The rapid development of clean energy, such as solar energy, wind energy and hydrogen energy, is expected to be the key to solve the energy problem. Several excellent literature works have highlighted quantum dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 155 publications
0
57
0
Order By: Relevance
“…However, when the lateral size of MXenes nanosheets is further reduced to nanometer size that is smaller than Bohr radius of the exciton (lateral size < 10 nm), shows strong photoluminescence, called zero-dimensional semiconductor nanomaterials—MXenes QDs (MQDs), which is an emerging branch of QDs (Fig. 2 ) [ 55 ]. In 2017 [ 56 ], Wang et al firstly reported the Ti 3 C 2 fluorescent ultrasmall monolayers MXene sheets by concurrent intralayer cutting and interlayer delamination.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the lateral size of MXenes nanosheets is further reduced to nanometer size that is smaller than Bohr radius of the exciton (lateral size < 10 nm), shows strong photoluminescence, called zero-dimensional semiconductor nanomaterials—MXenes QDs (MQDs), which is an emerging branch of QDs (Fig. 2 ) [ 55 ]. In 2017 [ 56 ], Wang et al firstly reported the Ti 3 C 2 fluorescent ultrasmall monolayers MXene sheets by concurrent intralayer cutting and interlayer delamination.…”
Section: Introductionmentioning
confidence: 99%
“…Different allotropes of carbon nanomaterials have been widely used as electrode materials for a wide range of sensing applications. Identical with graphene, graphene quantum dots (GQDs) are zero-dimensional nanoscale graphene fragments with diameters ranging from 5 to 20 nm. Because of their high electrical conductivity, chemical stability, and surface area for adjustment of the electrochemical performance, GQDs have attracted the attention of researchers . Additionally, GQDs show quantum confinement and edge effects.…”
Section: Introductionmentioning
confidence: 99%
“…Certain colorimetry and fluorometry-based analytical chemosensors, using organic dyes and nanoparticles, have been developed for the selective detection of tin ions. 24 26 These sensors have good selectivity but show poor sensitivity and reproducibility, thus providing limited detection efficiency. Also, these sensors are usually excited by high-energy light within the UV–vis region, making them less likely to be utilized in the biological system due to the short penetration depth of UV–vis light.…”
Section: Introductionmentioning
confidence: 99%
“…The direct methods, although provide good selectivity and sensitivity of detection, are expensive and tedious, which makes them unsuitable for real-time and in situ analysis. Electrochemical methods, which rely on differences in the redox potential of ions, have poor selectivity and reproducibility. Certain colorimetry and fluorometry-based analytical chemosensors, using organic dyes and nanoparticles, have been developed for the selective detection of tin ions. These sensors have good selectivity but show poor sensitivity and reproducibility, thus providing limited detection efficiency. Also, these sensors are usually excited by high-energy light within the UV–vis region, making them less likely to be utilized in the biological system due to the short penetration depth of UV–vis light.…”
Section: Introductionmentioning
confidence: 99%